Представления молодежи об элите и власти в России и Украине - Снежкова, И. (Народна творчість та етнографія, 2008)
On the basis of the Russian and the Ukrainian youth opinion poll the author of the article gives young people’s ideas of social elite and the authorities in Russia and Ukraine.